(3TQM MOjK CQHYjfs - (3eMeO Hf CHj HcQ GdYUahQjs ((3eMeO Hf EHQGgjes)
(3ChdgG (B:s
(3GdMeO ddg ZjQ Cfg hLO ef MOjK NjQ GdEfSGf UGMH GdeYLRGJ hGdHQgGf Cfg bGd ef LeY CQHYjf MOjKG agh aj GdYah hGdZaQGf aLeY GdYHO CQHYjf MOjKG HGdCSGfjO GdeJUdI Edi GdfHj Udi Gddg Ydjg hSde s
(3BNQgG (B:s
(3GdMOjK GdCQHYhf Yf GHf YHGS QVj Gddg Yfg bGd bGd QShd Gddg Ydjg GdSdGe jNQL aj BNQ GdReGf CbhGe hLhgge hLhg GdBOejjf hbdhHge bdhH TjGWjf hCeKGdge CeKGd GdPHGH GdVQGQj JeJ GdcJGHs
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeWHhYGJ GdYQHjI (B2\1331s
(3eYLe GdeWHhYGJ GdYQHjI (B2\1331s
(3eUOQ GbJfGA GdCUd (B:s
(3Ydj CejQjs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3GdMOjK hGdeUWdMs